ANALYSIS THE WETTED AREA FOR SUBSURFACE DRIP IRRIGATION IN DIFFERENT SOILS TEXTURE - Rasheed, Z. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Subsurface drip irrigation is one of the most efficient systems for management of water.  This study is aimed to analysis the wetted area for subsurface drip irrigation system.  Several models are developed for predicting the wetted widths and the wetted depths which are very important for designing an optimal irrigation system. HYDRUS/2D is used for predicting the dimensions of wetting patterns numerically by using the two dimensional transient flow of water from a subsurface drip irrigation through sandy loam and loamy sand soils.   The wetting patterns from a subsurface drip source are simulated by using the system of United States Department of Agriculture, USDA, the wetting patterns are simulated at different values of applied heads, different diameters of drip, and different values of initial volumetric soil water contents which selected as initial conditions.  In this work, greater spreading occurs in loamy sand than sandy loam in vertical and horizontal directions. Moreover, the results showed that the empirical formulas which can be used for estimating the wetting dimensions of wetted width and wetted depth in terms of initial volumetric soil water contents, applied heads, diameters of the drip and times of operation, are good with an average relative error not exceed 3%, so it can be used to assist the designers in irrigation field.